Reconstruction Of Contemporary Interpretation Theory An Examination Of Muhammad Arkoun's Thought - Umar Kustiadi (Institut Agama Islam Sumatera Barat, 2023)
Muhammad Arkoun, one of the modern Islamic thinkers, considers that the stagnation in the thinking of Muslims is still struggling with religious issues and has not moved from ready-made thoughts and without being assisted by thoughts that are initiative in accordance with current circumstances. The purpose of this study is to reveal how Arkoun offers his methodological study of the theory of reading the Quran, as well as how the correlation between the theory offered with the world of interpretation today. Basically, Arkoun has a desire for Muslims to become inclusive and tolerant people so that exclusive and intolerant thinking is dismantled and frozen. the issue of reading the Qur'an, Arkoun states that the Qur'an provides an infinite possibility of meaning. The appearance of a verse will always bring new interpretations, never certain and closed to a single interpretation. Arkoun's proposal is certainly a bold study in his reading of the Qur'an, because in it he re-questions the essence of revelation as the tresendent word of God and the discourse of revelation as a form of kalam in the immanent plain. Not a few Arkoun adopted some contemporary western science in interpreting the Qur'an, both linguistically, historically, anthropologically and others. These interpretive efforts have produced new interpretations that have never been done by Muslim scientists before.